Educación religiosa escolar en contextos plurales: lectura teológica del caso colombiano = School religious education in plural contexts theological reading of the Colombian case - Corpas de Posada, Isabel (Ciencias sociales y religión, 2012)
The purpose of a theological and at the same time interdisciplinary approach to the paradigm shift represented in the passage from an uniformistic view of the world to a pluralistic one, with the consequent changes in the religious field is to frame the practices of school religious education in the Colombian context. In order to identify this change, the communication typifies both paradigms in a series of representative texts interpreted from their corresponding contexts. As a conclusion, the difference between faith education and school religious education is considered: the first one supposes an intentionality within the religious tradition of Catholic Christianity as a confessional religious education for children from catholic families, while the second one offers a universalist vision of the diverse forms of religious experience and its corresponding forms of expression as a study of the religious fact in its diversity and its relation with social groups.